Ca2+ signalling in plant immune response: from pattern recognition receptors to Ca2+ decoding mechanisms. Issue 4 (24th September 2014) - Seybold, Heike; Trempel, Fabian; Ranf, Stefanie; Scheel, Dierk; Romeis, Tina; Lee, Justin
Summary: Ca 2+ is a ubiquitous second messenger for cellular signalling in various stresses and developmental processes. Here, we summarize current developments in the roles of Ca 2+ during plant immunity responses. We discuss the early perception events preceding and necessary for triggering cellular Ca 2+ fluxes, the potential Ca 2+ ‐permeable channels, the decoding of Ca 2+ signals predominantly via Ca 2+ ‐dependent phosphorylation events and transcriptional reprogramming. To highlight the complexity of the cellular signal network, we briefly touch on the interplay between Ca 2+ ‐dependent signalling and selected major signalling mechanisms – with special emphasis on reactive oxygen species at local and systemic levels.